Analisis Penerapan Karakter Disiplin Dan Tanggung Jawab Dalam Pembelajaran Ips Siswa Di Mts Nur Rahma Kota Bengkulu - Bela Ardila; Saepudin; M. Ilham Gilang (JURNAL ARMADA PENDIDIKAN, 2025)
This study aims to analyze the implementation of discipline and responsibility in Social Studies (IPS) learning at MTs Nur Rahma, Bengkulu City. Discipline and responsibility are two main components in character education that need to be instilled from an early age to shape students' strong and integrated personalities. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of two Social Studies teachers and 10 students at MTs Nur Rahma, Bengkulu City. The results show that Social Studies learning at MTs Nur Rahma is designed not only to achieve cognitive goals, but also to shape discipline and responsibility. Teachers foster these two characters through habituation, role models, and assignments that require active involvement and consistency from students. Obstacles faced include low student awareness, lack of parental support, and the influence of a less conducive environment and social media. Supporting factors include the support of the principal, a structured school habituation program, and teacher commitment. It is recommended that there be collaboration between schools, teachers, parents, and the community to create a supportive educational ecosystem, so that the values of discipline and responsibility are firmly embedded in schools and carried over into students' daily lives.